Survey of occupational stress among urban school librarians in Nigeria - Victor-Aigbodion, Vera (Universitas Negeri Padang, 2022)
Occupational stress is becoming increasingly common in all categories of workers. Due to the overwhelming demands of library customers, librarians are likely to suffer occupational stress as well. The objective of this study is to assess the occupational stress of urban school librarians in selected Nigerian public secondary schools. A descriptive survey was conducted and the Occupational Stress Scale (OSS) was used to collect data from 75 urban secondary school Librarians in South-East Nigeria. Means, standard deviations, and analysis of variance were used to analyze the results. Findings suggested that male and female secondary school librarians in the sampled urban secondary schools felt similarly about their occupation's level of stress. In addition, urban school librarians with bachelor's degrees reported higher levels of occupational stress. Another finding showed that urban school librarians who are married showed more occupational stress than those who are single, separated/divorced and widowed. Moreover, no significant differences were found between urban secondary school librarians who worked in mixed or single sex schools for occupational stress. In conclusion, occupational stress is present among urban school librarians in Nigerian public secondary schools. It was recommended that stress management interventions should be tailored to assist these school librarians in managing their level of stress.